How E-Commerce Shapes Cross-Border Trade in the Digital Era (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study explores the transformative effects of e-commerce on cross-border trade in the digital age, with a particular focus on the Balkan countries (Kosovo, Albania, Bulgaria, Bosnia and Herzegovina, Montenegro, Romania, Croatia, Serbia, northern Macedonia, Greece and Slovenia). It analyzes how the integration of electronic commerce reshapes traditional international trading practices by reducing geographical barriers and introducing new cost dynamics. Utilizing survey data from 300 e-commerce SMEs, the research investigates the impact of factors such as distance, language barriers, and emerging e-commerce costs on trade expenses. Through regression analysis, the study reveals that online transactions significantly lower distance-related costs, aligning with the "death of distance" concept. However, language barriers continue to pose a challenge. The findings also indicate that improvements in cross-border payment systems could lead to substantial increases in e-commerce activity. Furthermore, information-oriented business models and digital marketing strategies are identified as key drivers of sales growth and market success. The paper concludes with policy recommendations aimed at enhancing digital trade and fostering economic integration in the region. The research contributes to the understanding of e-commerce dynamics and its role in shaping future trade landscapes.